Isolation and characterization of Bordetella bronchiseptica bacteriophages using prophage induction and enrichment methods - Hadzevych, D. V.; Paliy, A. P.; Hadzevych, O. V.; Pavlichenko, O. V.; Dunaev, Y. K.; Keleberda, M. I.; Pastukhova, T. A.; Zhazharskyi, V. V. (Regulatory Mechanisms in Biosystems, 2026)
Bordetella bronchiseptica is an important bacterial pathogen of respiratory infections in companion animals and a promising target for bacteriophage application. However, the efficiency of isolating specific bacteriophages from clinical material remains low, and the factors associated with successful phage isolation have not been sufficiently studied. The aim of this study was to optimize methods for the isolation of B. bronchiseptica bacteriophages and to determine the factors associated with the efficiency of their isolation from clinical material. A total of 437 dogs and cats with and without sym p toms of respiratory diseases were examined. The presence of B. bronc hiseptica was determined using polymerase chain reaction and bacteriological methods. PCR was used as a confirmatory method for the presence of the pathogen, whereas bacteriological isolation of the culture was evaluated as an indicator of the presence of a viable bacterial host required for bacteriophage replication. Phage isolation was performed using the direct isolation method, as well as with the application of prophage induction, preliminary enrichment, and chloroform treatment. According to the PCR results, B. bronchiseptica DNA was detected in 124 of 437 animals (28.4 % ), whereas viable cultures of B. bronchiseptica were isolated only in 53 cases (12.1 % ). The highest frequency of bacteriological isolation of the pathogen was established in animals with an acute course of respiratory infection (31.7%), whereas significantly lower frequencies were observed in animals with a chronic course of respiratory disease and in animals without clinical signs of respiratory pathology ( 6.7 % and 1.4 % , respectively ) . When using the direct isolation method, bacteriophages were detected only in 3 of 124 PCR-positive samples (2.4 % ). In contrast, the use of a combined protocol including prophage induction, preliminary enrichment, and chloroform treatment made it possible to increase the frequency of bacteriophage isolation to 8.9 % (11 of 124 samples), which statistically exceeded the efficiency of the classical direct isolation method (OR = 3.9; 95 % CI: 1.0–15.0; P = 0.048). In bacteriologically positive samples, bacteriophages were isolated significantly more frequently than in samples positive only according to PCR results (OR = 7.1; 95 % CI: 1.5–34.0). Of the 11 isolated bacteriophages, 10 were obtained from animals with an acute course of respiratory infection. The obtained results indicate that the key factors for the effective isolation of B. bronchiseptica bacteriophages are the presence of a viable bacterial host and the acute phase of the infectious process. To increase the frequency of bacteriophage isolation, it is advisable to collect clinical material from animals with an acute course of bordetellosis and to use a combined protocol including prophage induction, preliminary enrichment, and chlor o form treatment.